RANCANG BANGUN ALAT PENGONTROLAN IRIGASI BERBASIS INTERNET OF THINGS - Lase, Fanotona; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2021)
Irrigation is a way of providing water supply to agricultural land. The irrigation control system in Indonesia still uses a manual system to open and close irrigation channels using traditional methods. The control and arrangement of irrigation channels based on the Internet of Things using the NodeMCU ESP8266 control board is a tool designed to help farmers irrigate farmland remotely in real time through the Blynk application. This tool made aims to increase the efficiency and effectiveness of the work of the farmers. The process of controlling the tool can be done anywhere and anytime when connected to the internet in realtime. Testing on the tools using rice paddy prototypes. In testing connectivity and speed, the average control delay is 00: 01.28s without any problems. Produce an irrigation control device based on the Internet of Things that uses the NodeMCU ESP8266 board and can make it easier for farmers to control and monitor irrigation systems remotely without having to come to the location manually.